2020
DOI: 10.1049/el.2020.1116
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature‐grown gallium arsenide photoconductors with subpicosecond carrier lifetime and photoresponse reaching 25 mA/W under 1550 nm CW excitation

Abstract: The authors show in this Letter that photoconductors based on GaAs grown at low temperatures can exhibit photoresponses as high as 25 mA/W under continuous-wave 1550-nm-wavelength illumination. It is achieved by using an optical Fabry-Pérot cavity in order to improve the external quantum efficiency and by decreasing the post-growth annealing temperature down-to 450°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In this study, a genuine travelling-wave behavior has been demonstrated as a first step toward photomixers with unprecedented performance. Recent promising optimization of the absorption of 1550-nm light in LT-GaAs [48] give us hope that this concept could be also promising to develop TW photomixers pumped by lowcost and powerful 1550-nm fiber lasers and amplifiers. A1.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a genuine travelling-wave behavior has been demonstrated as a first step toward photomixers with unprecedented performance. Recent promising optimization of the absorption of 1550-nm light in LT-GaAs [48] give us hope that this concept could be also promising to develop TW photomixers pumped by lowcost and powerful 1550-nm fiber lasers and amplifiers. A1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the extinction coefficient for subbandgap absorption in LT‐GaAs is not well known and it varies with the material growth conditions and annealing temperature. [ 31 ] Furthermore, due to the two‐step absorption process, the material absorption in LT‐GaAs at this wavelength increases non‐linearly with the incident power. [ 18 ] We therefore make an initial estimate of κ = 0.01 using previous studies that report ≈5% absorption of a 500 nm thick LT‐GaAs layer pumped with 80 fs pulses at 1.57 µm with an average incident power of 50 mW.…”
Section: Metasurface‐enhanced Subbandgap Absorptionmentioning
confidence: 99%